Isolates of bacillus thuringiensis from maranhão biomes with potential insecticidal action against aedes aegypti larvae (diptera, culicidae) - Vianaa, J. L.; Soares-Da-Silvac, J.; Vieira-Netad, M. R.A.; Tadeie, W. P.; Oliveiraf, C. D.; Abdallag, F. C.; Peixotoh, C. A.; Pinheiroi, V. C.S. (Brazilian Journal of Biology, 2021)
Entomopathogenic agents are viable and effective options due to their selective action against insects but benign effects on humans and the environment. The most promising entomopathogens include subspecies of Bacillus thuringiensis (Bt), which are widely used for the biological control of insects, including mosquito vectors of human pathogens. The efficacy of B. thuringiensis toxicity has led to the search for new potentially toxic isolates in different regions of the world. Therefore, soil samples from the Amazon, Cerrado and Caatinga biomes of the state of Maranhão were evaluated for their potential larvicidal action against Aedes aegypti. The isolates with high toxicity to mosquito larvae, as detected by bioassays, were subjected to histological evaluation under a light microscope to identify the genes potentially responsible for the toxicity. Additionally, the toxic effects of these isolates on the intestinal epithelium were assessed. In the new B. thuringiensis isolates toxic to A. aegypti larvae, cry and cyt genes were amplified at different frequencies, with cry4, cyt1, cry32, cry10 and cry11 being the most frequent (33-55%) among those investigated. These genes encode specific proteins toxic to dipterans and may explain the severe morphological changes in the intestine of A. aegypti larvae caused by the toxins of the isolates.
Keywords: mosquito vectors; entomopathogenic bacterium; cry and cyt genes; histology